The Relationship of Vitamin D Giving on Blood Pressure of Pregnant Women - St. Munawwarah. M (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
Vitamin D is an important prohormone because vitamin D receptors (VDR) are present in many cells and tissues throughout the body. This research method is quantitative with a cross sectional study approach. This research was carried out in Makassar in 2021, the sample taken was 100 people. Analysis of the data used using the chi square test with = 0.00 provided that if the value of p <0.05 then there is a significant relationship between the dependent and independent variables. The data were analyzed using SPSS Version 23. The results of this study with a significance value of 0.00, it means that there is a relationship between giving Vitamins D to Blood Pressure. the intake of nutrition and vitamins for pregnant women should be a concern so that it becomes a preventive effort in preventing premature death and other pregnancy diseases, health workers and all stakeholders are expected to be able to take their respective roles.